Internet of Things for Smart Environment and Integrated Ecosystem - Thapliyal, Renu; Kumar Patel, Ravi; Kumar Yadav, Ajit; Singh, Akhilesh (International Journal of Engineering and Technology, 2018)
Internet of things (IoT) is in increasing demand in our daily life. This is the technology that transforms the real-time system into the virtual system and makes the communication in between machines. The rapid growth of IoT can be easily noticed in industries like home automation, transport, robotics, environment, energy, water domain etc. The IoT is a technological revolution that represents the future of computing and communications, and its development depends on dynamic technical innovation in a number of important fields, from wireless sensors to nanotechnology. They are going to tag each object for identifying, automating, monitoring and controlling. The aim of this paper is to give an overview of introduction, history, architecture, real-time application, challenges and future aspects of IoT along with statistics and its application in monitoring for future.Â Â